The Effect of E-learning On Student Learning Motivation on Campus - Nugroho, Dean; Kurniawanr, Sandi; S, Petrus Patria; Patrio, Paulus; Renaldy, Dizza; Nugraha, Ucu (CENTRAL ASIA AND THE CAUCASUS, 2022)
Background The research aims to see the effect of E-Learning on student learning motivation on campus. The population of this study is students throughout Indonesia who have studied using E-Learning in the semester of May 2019 with a total of 48 people. Sampling used the technique of distributing questionnaires by using the most voting method so that there were 48 respondents for research and 48 respondents for trials. The results showed that there was a relationship between the use of E-Learning and students' learning motivation. This value means it has a high relationship. Furthermore, data analysis of the use of E-Learning learning is carried out on students' learning motivation